Ecological Analysis of the Prevalence of Pulmonary Tuberculosis in Indonesia - Mara Ipa; Agung Dwi Laksono (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Previous studies have found that the potential loss of pulmonary tuberculosis is relatively high. The study aimed at analyzing ecologically the factors related to the prevalence of pulmonary tuberculosis in Indonesia.Methods: Ecological analysis conducted using secondary data from the Ministry of Health of the Republic of Indonesia report in 2018. All provinces take as samples. Apart from pulmonary tuberculosis, five other variables analyzed as independent variables were smokers’ percentage and adequate ventilation. Percentage of proper lighting, the rate of poor people, and the portion of the population completing primary education. Data were analyzed using a scatter plot.Results: The study results found that the higher the percentage of smokers in a province, the higher the prevalence of pulmonary tuberculosis. The higher the percentage of adequate ventilation in an area, the lower the prevalence of pulmonary tuberculosis. The higher the rate of sufficient lighting in a province, the lower the prevalence of pulmonary tuberculosis. Meanwhile, the higher the percentage of poor people in a region, the higher the prevalence of pulmonary tuberculosis. Finally, the higher the portion of the population completing primary education in a province, the lower the prevalence of pulmonary tuberculosis.Conclusion: It concluded five independent variables analyzed were related to Indonesia’s prevalence of pulmonary tuberculosis.